Shareholders’ Monitoring and Online Disclosures of Minutes of Shareholders’ Meeting - Mohd Shazwan Mohd Ariffin; Wan Nordin Wan-Hussin; Siti Seri Delima Abdul Malak; Ili Syahirah Kamaruzaman (Asian Academy of Management Journal, 2024)
Making detailed annual general meeting (AGM) minutes available online allows absentee investors to understand the discussion that took place during the AGM, and other interested parties to gauge the intensity of investor activism and stakeholder engagement from the questions posed. This paper investigated the effects of shareholders’ monitoring through the Minority Shareholders Watch Group (MSWG), the Employees Provident Fund (EPF), and other government-linked institutions on corporate communication via minutes of shareholders’ meeting. This study also incorporated firm size, audit quality, profitability, and grey directors as control variables. Based on a sample of 261 listed firms with financial year ended 31 December 2016 who held their AGMs in 2017, the findings showed that shareholders’ monitoring through the MSWG, EPF, and other government- linked institutions were significant and positively associated with corporate transparency. This implies that minority and institutional shareholders’ activism can be the advocate in pushing for dissemination of online corporate disclosure to enhance the information environment, in align with agency theory.